(untitled) ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2026)
This study looks at the structural, semantic, and cultural aspects of eco-lexicon expressions in Uzbek and English. An essential part of ecolinguistics, eco-lexicon represents environmental consciousness and how nature is conceptualized in language. The study examines how ecological vocabulary is formed in both languages through compounding, affixation, and metaphorization using descriptive and comparative-typological methods. The results show that although Uzbek eco-lexicon preserves culturally distinctive and context-dependent meanings derived from national ecological experience, English eco-lexicon is primarily standardized and affected by global environmental discourse. In addition to offering useful implications for translation and environmental education, the study advances cross-linguistic ecolinguistic research.